Dissolved organic matter derived from biodegradable microplastic promotes photo-aging of coexisting microplastics and alters microbial metabolism - Ouyang, Zhuozhi; Li, Shuxing; Xue, Jincheng; Liao, Jinmo; Xiao, Chuanqi; Zhang, Hong; Li, Xiaohan; Liu, Peng; Hu, Shiwen; Guo, Xuetao; Zhu, Lingyan (Journal of hazardous materials, 2023)
Dissolved organic matter (DOM) leaching from biodegradable microplastics (BMPs) and its characteristics and corresponding environmental implication are rarely investigated. In this study, the main component of DOM leachate from the two BMPs (polyadipate/butylene terephthalate (PBAT)/polycaprolactone (PCL)) was verified by using excitation-emission matrix-parallel factor analysis (EEM-PARAFAC). The PBAT-DOM (PBOM) was aromatized and terrestrial. Comparatively, PCL-DOM (PLOM) had low molecular weight. PBOM contained protein-like components while PLOM contained tryptophan and tyrosine components. Interestingly, both PBOM and PLOM could accelerate the decomposition and oxidation of coexisting polystyrene (PS) under light irradiation. Further, the difference in composition and the properties of BMPs-DOM significantly affected its photochemical activity. The high territoriality and protein-like component of PBOM significantly promoted the generation of 1O2 and O2•-, which caused faster disruptions to the backbone of PS. Simultaneously, the microbial community's richness, diversity, and metabolism were obviously improved under the combined pressure of aged PS and BMPs-DOM. This study threw light on the overlooked contribution of DOM derived from BMPs in the aging process of NMPs and their impact on the microbial community and provided a promising strategy for better understanding of combined MPs' fate and environmental risk. [Display omitted] •The components of DOM leaching from BMPs were identified.•The photo-aging process of PS induced by BMPs-DOM was quantitatively investigated.•The presence of BMPs-DOM accelerated the decomposition and oxidation of PS.•The properties and components of BMPs-DOM affected the production of ROS.•The microbial metabolism was altered under the pressure of BMPs-DOM and aged PS.